Penerapan Pembiayaan Gadai Emas Syariah di BMT Sidogiri - Baihaki, Imam (At-Turost : Journal of Islamic Studies, 2023)
Pawn is a type of agreement that has existed in society for a long time, starting from customary pawn, conventional pawn, to sharia pawn. In Islamic Law, sharia pawning is known as rahn, which is a type of agreement to hold an item as a debt liability and is carried out by a sharia pawnshop. The author is of the opinion that one of the sharia pawn products, namely sharia gold pawning transactions, is the right choice when there is an urgent financial need. This is the basis for the author's interest in the theme of sharia gold pawning. This study examines the general description of pawnshops in Indonesia, the requirements and procedures for implementing sharia gold pawning at BMT UGT Sidogiri capem Arjasa Situbondo, as well as supporting factors for sharia gold pawning as an alternative financing at BMT UGT Sidogiri capem Arjasa Situbondo. This research is normative legal research with descriptive research type. The problem approach used is a normative legal approach. The data used is secondary data consisting of primary, secondary and tertiary legal materials. Data collection was carried out by means of literature study, document study, and interviews with informants who use sharia pawn services. The results of the study show that the general description of pawnshops in Indonesia divided into two, namely conventional pawnshops which are regulated in the Civil Code and PP No. 51 of 2011 concerning Persero Pawnshops and Sharia Pawnshops which are based on the provisions of Islamic law, namely the Al-Quran, Al-Hadith, and Fatwa No. 25/DSN/MUI/III/2002 concerning Rahn (Pawn). The terms and procedures for sharia gold pawning are fulfilling the legal requirements of the agreement as on the legal basis of Article 1320 of the Criminal Code coupled with the financing requirements submitted by the sharia pawnshop itself. The procedure uses a rahn contract and an ijarah contract. The factors that make Islamic gold pawning an alternative to financing at BMT UGT Sidogiri capem Arjasa Situbondo are the absence of usury/interest and lower costs as well as the security of collateral.